PULMONARY CAPILLARY HEMANGIOMATOSIS: A RARE CAUSE OF PULMONARY ARTERIAL HYPERTENSION, PRESENTING AS SUPRAVENTRICULAR TACHYCARDIA - Dattaprasad, Ganganpalli; Chandra, Umesh Kumar; Vishwakarma, Sumit Kumar; Pandey, V.P.; Dubey, Sanjay (International Journal of Cardiovascular Practice)
With a prevalence of less than 1/million, Pulmonary Capillary Hemangiomatosis is a rare disorder of capillary proliferation in the alveolar septae leading to pulmonary arterial hypertension and mimics pulmonary veno-occlusive disease.